(untitled) (Fountain Journal of Natural and Applied Sciences, 2012)
Well-water samples were collected from the vicinity of Balogun–biiro dump-site located in Okebaale Oshogbo, Osun state, Nigeria. The aim of this research work is to provide background information on the concentration of n-alkanes in the well-water in order to assess its pollution status and probable sources. The n-alkane was determined qualitatively and quantitatively using GC-FID. The concentration of n-alkanes in the water samples was, 8.07, 9.64, 9.75, 8.43, 10.4, and 10.1 mg/L in S1, S2, S3, S4, S5, and S6 respectively. The highest concentration of n-alkanes was recorded in the water samples collected from a well located in a residential building very close to the dumpsite as well as the mechanic workshop (i.e. S5) while the lowest concentration was recorded in S1 (well-water relatively far from the dump-site). Various n-alkanes diagnostic ratios obtained indicated anthropogenic sources (i.e. both petrogenic and pyrogenic) and showed moderate level of pollution in the area under study. Keywords: GC-FID; aliphatic hydrocarbon; pollution; anthropogenic; mechanic workshop